Mission driven by fear and despair: The case of Kranspoort – the first Dutch Reformed Church mission station outside the Cape Colony - Kgatla, ST (Stellenbosch Theological Journal, 2016)
This article surveys the Dutch Reformed Church Mission Policy and the close collaboration of mission and politics. The 1948 Nationalist Party election victory brought about a host of laws designed to bring total control and dominance over black people’s lives and their destiny. The Dutch Reformed Church was drawn into the government agenda to the extent that they lost their prophetic voice. The use of government instruments such as the forced removal of ‘excess’ and unwanted people from white farms was employed by the church. Black Christians that held a different political view were declared “no longer Christians” and forcefully removed from the mission stations. The pious outlook of mission did not help the church to realise that its social and political interests were against the love of Christ and thus the love of the neighbour.